The path to Police and Crime Commissioners. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to explore the key political factors behind the introduction of Police and Crime Commissioners (PCCs) and attempt to address some of the major tensions in the democratic governance of the police.Design/methodology/approach – Using a literature review, the paper examines the changing face of police accountability in England and Wales over the last 50 years.Findings – Three critical insights emerge from this analysis. First, the politicization of the police began in the 1980s – well before the introduction of PCCs – and was in fact one of the key antecedents behind the introduction of PCCs. Second, the paper finds that the simultaneous growth of managerialist practices further enabled politicians to interfere with policing in ways which eventually laid the foundation for PCCs. Lastly, the investigation illustrates how the policy architecture then drew inspiration from models of police governance from the USA, which chimed well with a new generation of Conservatives intent on police reform.Originality/value – The paper offers a unique policy history which helps to better understand the political rationale behind PCCs and helps to clarify the underlying trajectory of the policy. Acknowledgements : The author would like to acknowledge the Police Foundation and Green Templeton College for the collaborative doctoral studentship which funds his PhD.